Virtual reality and augmented reality technologies: A closer look - Renas Rajab Asaad (Northern Negros State College of Science and Technology (NONESCOST), 2021)
Virtual Reality (VR) and Augmented Reality (AR) technologies are based on the creation of a completely new scene that cannot be touched by the bare hand but is sensually perceived through a combination of artificial visual and sound effects. Although the overall goal of these two technologies is similar, the artificial reality that can be created via VR or AR is not the same. VR is a computer-generated simulation of an alternate world or reality, primarily used in 3D movies and video games. Virtual reality creates a simulation that aims to close off the outside world or immerse the viewers, using computers and sensory equipment such as headphones and gloves. The HTC Vive, Samsung Gear VR glasses, and Google cardboard are some of the most popular devices used in VR. Virtual reality applications are not limited to entertainment and games only, but are also used in the field of education and medicine, for example, surgeons plan and train their operations, and it has also been used in the military field to simulate some military exercises under harsh conditions.